Design of 3-stages Parallel Cascade Micro-ring Resonator Type of Interleave Filter for Optical Communication Application - Yudi Yuliyus Maulana; Dadin Mahmudin (National Research and Innovation Agency, 2015)
Filter will be one of the most important components of the next generation of optical communications. Micro-ring resonators have been widely studied as a potential device for dense wavelength filter due to its advantages. In this paper, a waveguide-based microring-resonator type of interleave filter is investigated. The cascade structure is applied to obtain better characteristics of filter spectra. Our calculation shows that, compared with 2-stage or 4-stage cascade, 3-stage cascaded microring resonator has better performance with pass-band width of 22 GHz, ripple ratio < 1 dB, crosstalk of -33 dB for 1×2 interleaver and -24 dB for 1×4 interleaver. Numerical calculation also clearly shows that general optical waveguide types is reasonable as microring resonator with insertion loss < 2 dB